Respuesta :

Answer:

A

Step-by-step explanation:

The explicit formula for a geometric sequence is

[tex]a_{n}[/tex] = a₁ [tex](r)^{n-1}[/tex]

where a₁ is the first term and r the common ratio

The recursive formula gives a term in the sequence by multiplying the previous term by r

Given the recursive formula

a₁ = - 6

[tex]a_{n}[/tex] = [tex]a_{n-1}[/tex] ([tex]\frac{1}{4}[/tex] )

with r = [tex]\frac{1}{4}[/tex]

Then explicit formula is

[tex]a_{n}[/tex] = - 6[tex](\frac{1}{4}) ^{n-1}[/tex] → A

ACCESS MORE